A new design of unsymmetrical shunt circuit with negative capacitance for enhanced vibration control. (16th June 2021) - Ji, Hongli; Guo, Yufei; Qiu, Jinhao; Wu, Yipeng; Zhang, Chao; Tao, Chongcong
Highlights: The circuit designed by simple electronic components realizes unsymmetrical voltage. Parameters in circuit that affect unsymmetrical voltage and stability are discussed. The circuit increases the effective voltage range on PZT and improves control effect. The offset resistance plays an important role in the stability of the system. Abstract: Piezoelectric elements are widely used in structural vibration suppression. The applicable bipolar voltage of a piezoelectric element is unsymmetrical, but in most control systems, the voltage on the piezoelectric actuator is applied symmetrically, which greatly wastes the driving capability. In synchronized switching damping (SSD) approaches for structural vibration control, the damping effect depends on the effective voltage range on the piezoelectric actuator. A novel method of realizing unsymmetrical bipolar voltage with SSD method based on negative capacitance shunt circuit for vibration control is proposed for improvement of the control performance in this study. A resistance and a diode that added into constructed negative capacitance circuit are used to realize unsymmetrical bipolar voltage. The general expression of the switched voltage on the piezoelectric actuator is derived. The stability of negative capacitance shunt circuit is addressed. The added offset resistance in the negative capacitance circuit plays an important role in system stability. The simulation analysis results agree very well with the theoretical results, both of which reveal that the unsymmetrical voltage ratio depends on the resistance in the negative capacitance circuit. Finally, experiments are carried out to verify the designed circuit and the excellent damping performance.